Familial Translocation t(2;4) (q37.3;p16.3), Resulting in a Partial Trisomy of 2q (or 4p) and a Partial Monosomy of 4p (or 2q), Causes Dysplasia - Wang, Jian; Zhou, Shiyuan; He, Fei; Zhang, Xuelian; Lu, Jianqi; Zhang, Jian; Zhang, Feng; Xu, Xiangmin; Yang, Fang; Xiong, Fu (Frontiers in Genetics, 2021)
Background: Wolf-Hirschhorn Syndrome (WHS), a well-known contiguous microdeletion syndrome, is caused by deletions on chromosome 4p. There have been many related studies on it. The clinical symptoms and the critical region for this clinical disorder has been narrowed based on the genotype-phenotype correlations. However, duplications in this region have been reported infrequently. Case presentation: We report on a family showing a set of dysmorphic facial features, attention deficit hyperactivity disorders, learning difficulties, speech and cognitive delays, overgrowth/developmental delay, and musculoskeletal anomalies. Through karyotype analysis and chromosome microarray analysis combined with PCR Results, we found that patients in this family had translocations on chromosomes 2q37 and 4p16. Patients with 2q duplication and 4p deletion showed typical clinical phenotype of WHS syndrome, and family members with 2q deletion and 4p duplication also had obvious clinical phenotype. Conclusions: Our case report shows that not only deletions but also duplications of the Wolf-Hirshhorn critical region cause mental retardation and multiple congenital anomalies.